CHET TILLARINI O’SPIRIN YOSHDAGI O’QUVCHILARGA O’RGATISHDA PSIXOLOGIK YONDASHUVLARNING AHAMIYATI - Djolimbetova, M.M.; Sultamuratova, X.N. (SCIENCE and SOCIETY, 2022)
The given article discusses the psychological nature of teenagers, their psychological changes, English language teaching techniques, and the role of psychological approaches in teens foreign language learning.
Keywords: acceleration; biogenetic orientation; early adolescence; psychogenetic orientation; temperament